Comparative study of closed reduction and internal fixation of supracondylar fracture of humerus in children by lateral pinning and cross pining - Samrat, Mohsin Hasan; Islam, Ismat Ara; Hasan, Md Rakibul; Alam, Md Iftekharul; Hasnat, Muhammad; Dam, Asit Baran; Islam, Md Saiful (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: Supracondylar injuries of the humerus are the most prevalent elbow injury among pediatric patients. The conventional treatment of displaced fractures involves closing the reduction as well as percutaneous Kirchner wire pinning, using either lateral pin fixation or cross pin fixation. The objective of the study is to evaluate and contrast the results of lateral vs bilateral percutaneous pinning in pediatric patients with supracondylar humeral injuries. Methods: A comparative cross-sectional study was conducted at the National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR) between July 2017 to June 2019. Children were classified into two groups according to the percutaneous pinning technique: Lateral pinning (n=15) and Crossed pinning (n=15). Both groups were comparable in terms of age, gender, injury duration, along with degree of fracture displacement. The chi-square test and t-tests for independence were employed. The results were reported as mean, frequency, along with percentage, with P < 0.05 indicating statistical significance, using SPSS software. Result: The average age of patients was 6.86 ± 2.53 years for group I and 6.57 ± 2.41 years for group II overall. In the cohort with dual lateral K-wire fixation, 20% achieved exceptional outcomes, 66.67% obtained good outcomes, and 13.33% realized fair outcomes. In the medial-lateral K-wire fixation cohort, 20% achieved exceptional outcomes, 60% attained satisfactory results, and 20% exhibited acceptable results, with a P value of 0.881, signifying statistical insignificance. In the medial-lateral cross K-wire fixation group, the incidence of iatrogenic ulnar nerve injuries was 6.67%, while the two lateral K-wire fixation group reported no neurological injuries, yielding a P value of 0.664. Thus, the difference in the incidence of ulnar nerve injury between the two patient cohorts was not significant. Conclusion: Both fixation methods exhibit effectiveness; the application of two lateral K-wires offers stability akin to medial-lateral cross K-wire fixation while mitigating the danger of iatrogenic ulnar nerve injury. J Shaheed Suhrawardy Med Coll 2024; 16(1): 7-13